(3GdeMJVQs - (3GdYGedj GdMdj, MSf Hf SdjeGf Hf eMeO Hf NGdO, cGf MjG (B802 (3g`s ((3eTgO CHj GdCFeI Ydjg GdSdGes)
(3ChdgG (B:s
(3GdMeO ddg (B... (3abO PcQ GdTjN GdSYjO GdeajO eMeO Hf eMeO Hf GdfYeGf GdMGQKj QVhGf Gddg Ydjg aj cJGHg GdebGdGJ eG McGjJg Gdbhd aj QDjI GdeMJVQ aj QShd Gddg Udi Gdg Ydjg hSde hCejQ GdeDefjf Ydjg GdSdGe(B...s
(3BNQgG (B:s
... (3dGf efGbHge NGQLI Yf MO GdMSGH hdG jMjW HEMUGFgG GdcJGH YOO Cbd dh cGf GdHMQ eOGOG dcdeGJ QHj dfaO GdHMQ bHd Cf JfaO cdeGJ QHj hdh LFfG HeKdg eOOG (B.s
(3efbhdI Yf fSNI (B: (3GdTjN TjQ eMeO Hf UaQ Ydj GdgePGfj GdLhQbGfj Yf fSNI Yf fSNI Yf fSNI HNW GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B1 - 256 ( 2155)s
(3GdPQjYI (B20 - 98 (2308)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds